World Investment Report 2024 - UN Trade; Development (United Nations, 2024)
Business and investment facilitation have become central to both private sector development and FDI attraction efforts of governments in developing countries. At the core are information provision, transparency of rules and regulations, and streamlining of administrative procedures. Because these elements are information- and procedures-based, digitalization is central to effective implementation. They have thus led to a wave of digital government initiatives, including information portals and online single windows. Digital government has the potential to address many institutional challenges faced in developing countries, strengthening governance, reducing costs, improving services, and combating corruption. Because governance and institutional weaknesses are a key obstacle to attracting investment in many developing countries, digital government and the promotion of investment for sustainable development are closely intertwined.